(untitled) (Al-Farooq Journal of Sciences, 2026)
This study investigated the role of encryption techniques in protecting student and faculty data during the digital transformation of Libyan educational institutions (Faculty of Economics, Al-Ajaylat as a case study). A descriptive-analytical approach was employed, with data collected via an electronic questionnaire from (100) participants. The findings revealed a high level of awareness regarding encryption importance (Mean: 4,2). and a strong perception of its role in enhancing digital trust (Mean: 3.90). However, the study identified significant technical challenges (e.g., system complexity and performance issues) and human challenges (e.g., lack of specialized expertise) that hinder effective implementation. The study recommends upgrading encryption protocols to (AES-256) standards, implementing Multi-Factor Authentication (MFA), and bridging the gap between theoretical awareness and practical application through specialized training programs.